Historicity of The Resurrection: A Theological Approach of Evidence of The Resurrection of Christ In The New Testament - Made Astika (Jurnal Jaffray, 2012)
Jesus is the resurrection and the life. He'll never wear grave clothesagain. When he appeared to his disciples after the resurrection, heappeared not in a shroud of death, but walking in endless life.The Lord Jesus is the Son of God who became man. He is very Godand very man. He was crucified, he died and was buried, and he wasraised from the dead on the third day according to the Scriptures.The proofs of resurrection can be found both in the Scripture andalso in the history. Historically, the empty tomb and Jesus appearancesto His disciples and many of His followers are clear proving that theresurrection of Chris is real. Biblically, it was the main preaching andteaching of the apostles. Beside that Jesus Himself prophesied andteaches about His resurrection.These three great facts--the resurrection appearances, the emptytomb, and the origin of the Christian faith--all point unavoidably to oneconclusion: The resurrection of Jesus. Today the rational man can hardlybe blamed if he believes that on that first Easter morning a divine miracleoccurred. Further fact is, if no resurrection, there will no church, therewill no Christianity. Because of Jesus resurrection, the believers haveassurance future life. Because He lives, there is hope for the future; thereis certain hope for the salvation of the believers.